2021
DOI: 10.11648/j.sr.20210902.11
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cattle Husbandry Practices and Coping Strategies Against Feed Scarcity in Buno Bedele Zone, South Western Ethiopia

Abstract: The study was aimed with to study dairy cattle husbandry practices and coping strategies against feed scarcity in selected districts of Buno Bedele zone, south western Ethiopia. Both purposive and simple random sampling techniques were used to select kebeles and household respondents. For this study, a total of 384 households were used for an interview. Of the total land size occupied by the respondents, higher proportions (5.07±2.739) were used for communal grazing land followed by land for cereal production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Dairy farmers used two sources to water their cattle ( Table 5 ); either from the river (54.3%) or from pipe (45.8%). ( Tesfaye and Wondossen, 2019 ) for Gurage Zone, ( Bekuma and Addisu, 2021 ) for Buno Bedele Zone, and Hosanna town have all indicated such water sources. Similar to the Alefa district of North Gondar Zone ( Ayeneshet et al., 2018 ), near half of (44.1 %) of dairy producers in Dilla Zuriya provided water twice a day.…”
Section: Resultsmentioning
confidence: 99%
“…Dairy farmers used two sources to water their cattle ( Table 5 ); either from the river (54.3%) or from pipe (45.8%). ( Tesfaye and Wondossen, 2019 ) for Gurage Zone, ( Bekuma and Addisu, 2021 ) for Buno Bedele Zone, and Hosanna town have all indicated such water sources. Similar to the Alefa district of North Gondar Zone ( Ayeneshet et al., 2018 ), near half of (44.1 %) of dairy producers in Dilla Zuriya provided water twice a day.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study in Dilla, Gedeo Zone, by Hailemariam et al (2022) reported that dairy farmers used two sources to water their cattle, either from the river (54.3%) or from pipes (45.8%) and also (Tesfaye and Wondossen, 2019) for Gurage Zone and (Bekuma and Addisu, 2021) for Buno Bedele Zone, which have all indicated such water sources. This study contradicted the findings of Bereda et al (2012), who discovered that the majority of dairy cow producers in the Gurage zone used river and hand-dug well water, which may not be of the required standard.…”
Section: Discussionmentioning
confidence: 96%
“…The altitude of the Bedele, Dabo, Gechi and Boracha district are 1294–2374, 1268–2267, 1488–2384 and 1332–2292 m above sea level, respectively. The major animal feed over the entire study area is crop residues, followed by natural pasture [ 15 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%